Living with a chronic health condition: Students' health narratives and negotiations of (ill) health at university. (October 2018) - Spencer, Grace; Lewis, Sophie; Reid, Megan
Objective: Increasing numbers of young people live with a chronic health condition. Much research to date has explored young people's self-management of their illness and related symptomatology. Relatively less is known about how young people manage their long-term condition in everyday social contexts. This paper reports on findings from a qualitative study examining the perspectives of university students with a chronic health condition, including how they negotiate their health (and experiences of ill health) while at university. Design: A qualitative interview study was conducted with 16 students with a medically diagnosed chronic health condition. Setting: The study was conducted at a major university in Australia. Methods: Data were collected via in-depth semi-structured interviews and analysed thematically and inductively. Results: Findings illustrate how young people sought to position themselves as being 'healthy' while simultaneously distancing themselves from labels of ill health and disability. The relative invisibility of their health conditions enabled participants to align with and enact a preferred health identity. Yet, this invisibility presented particular challenges for students when navigating university systems and processes. Indeed, the fluctuating nature of their (ill) health status prompted a felt need continuously to prove their ill health to the university in order to receive academic support. Inevitably, this illness identity was at odds with participants' own health narratives – triggering additional anxieties and (academic and social) exclusions for these young people. Conclusion: These contradictory (ill) health positions carry a number of implications for how best to support young people living with chronic health conditions while at university.